IS L. WITTGENSTEIN A PHILOSOPHER OF ANALYTIC OR HERMENEUTIC? - Tomas Kačerauskas (Problemos)
The purpose of the article is to show a contraversion of analytic and hermeneutic, the philosophy of explanation and understanding on basis early (Tractatus Logico Philosophicus) and late L. Wittgenstains (Philosophical Investigations) masterpieces. The linguistic turn of Tractatus means a reduction of philosophical problems to the problems of logical semantic. It is posible, because early Wittgenstain supose an unified logical space. The meaning is an equivalent of a proposition and a fact. This "gramatic" supose an unified ontology of the world and his perception. This ontology is close to phenomenological looking. The ideas of early Wittgenstein are most original and influential comparing with Frege's, Russel's and Carnap's views. The author of Philosophical Investigations modifies the problems of explanation to the problems of understanding. The variety of language games dosn't supose epistemic monism. So appears philosophy of speech instead of philosophy of language. Then the tasks of philosophy are regrounded. As philosophy or relativism Investigations are close to philosophy of Nietzche and Heidegger. But the understanding is without ontology. It is an adaptation usage mastering the technique. The picture as a ground of understanding links early and late Wittgenstein. The picture is given with speech, and a harmony of thought and facts in a picture is the understanding. Late Wittgenstein influenced the late hermeneutic and pragmatic analytic.